Surface Engineering and Applied Electrochemistry - Bologa, Mircea K.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
This journal publishes both theoretical and applied articles dealing with a broad spectrum of topics in surface engineering and applications of electrochemistry in industrial processing. It covers the methods and processes of electrical treatment of materials, utilization of electrical fields, currents and charges, improvement of existing technologies, intensification of heat-and-mass transfer processes, and treatment of biological media and foodstuff. The journal includes sections on equipment and instrumentation, as well as information on significant events and reviews in the field.
Keywords: Manufacturing industries; Machines; Tools; Manufacturing, Machines, Tools